CRITERIA OF POSITIVITY FOR Ig ANTIBODIES IN THE METHOD OF IMMUNE BLOTTING OF LYME DISEASE - V G Barskova; L P Ananieva; V A Nassonova; A. S. Steere (Научно-практическая ревматология, 2001)
There are currently no accepted criteria for positive Western blots in Russian patients with Lyme borreliosis. The purpose of the current study was to develop criteria for a positive IgG westem-blot to aid particularly in the diagnosis of patients with joint manifestation of the disorder. Patients: 97 with Lyme disease, 145 - control subjects. IgG antibody responses were determined to 3 species ofB.burgdorferi sensu lato by Western blotting, using blots prepared by manufacturer. The best discriminatory ability of test criteria was chained by requiring any 3 of 11 IgG bands, a definition that could be used with B. burgdorferi sensu stricto, B.garinii and B.afzelii strains. With these 3 antigen preparation, positive IgG blots were found in 0 to 18% of patients with localized erythema migrans of < 4 weeks duration, 23 to 39% of those with disseminated infection < 20 weeks duration, and in 39 to 46% of those with late arthritis/arthralgia of >6 months duration the specificity was 93 to 99%. Thus, IgG Western blotting may bring greater specificity to serologic testing in Lyme borreliosis, but the sensitivity is limited.